Three dimensional building reconstruction based on airborne LiDAR, aerial photogrammetry and topographic datasets / Roslina Idris - Idris, Roslina (Institute of Graduate Studies, UiTM, 2016)
3D building model of man-made objects supports a diversity of applications such as urban planning, flood mapping and telecommunication. At present, a total automation towards the construction of a detailed and accurate 3D city model is not possible. In order to reduce the time of constructing the 3D building models, an integration of reliable dataset is explored. In mapping technologies, sophisticated sensor has been developed to serve the mapping community. Airborne LiDAR (Light Detection and Ranging) technology has changed the conventional method of topographic mapping, and the increasing interest of these valued datasets for the construction of 3D building models is an active research agenda. Airborne LiDAR provides three dimensional (3D) information of the earth surface with high accuracy point clouds. In this study, the capability of remotely sensed data for the reconstruction of 3D building models is explored, namely; LiDAR dataset, aerial images, digital topographic information and terrestrial photographic images. The study area comprised of residential buildings situated in Putrajaya within the Klang Valley region, Malaysia, covering an area of two square kilometers. The process of the reconstruction 3D building model includes integration of LiDAR dataset, aerial photo, digital topographic information and low cost terrestrial images couple with processing software namely the ArcGIS and SketchUp. Valuable building parameters are extracted based on automated retrieval from the normalized Digital Surface Model (nDSM) as a result from LiDAR DSM and LiDAR Digital Terrain Model (DTM) separation…